2017
DOI: 10.1177/1756283x17734116
|View full text |Cite
|
Sign up to set email alerts
|

Use of beta-blockers and risk of serious upper gastrointestinal bleeding: a population-based case-control study

Abstract: Background:Some studies indicate a reduced risk of serious upper gastrointestinal bleeding (UGIB) for users of beta-blockers, but the association remains to be confirmed in larger studies and characterized with respect to differences among beta-blockers. We aimed to assess whether beta-blocker use decreases the risk of UGIB.Methods:We conducted a register-based, population-based case-control study in Denmark. We identified cases with a first validated discharge diagnosis of UGIB during the period 1995–2006. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Case-control studies found associations of calcium channel blockers with increased gastrointestinal bleeding; however, this finding was not confirmed by subsequent studies . Nonselective β-blockers are associated with reduced bleeding from gastroesophageal varices in patients with cirrhosis, but in more general populations, β-blockers are not associated with upper gastrointestinal bleeding …”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies found associations of calcium channel blockers with increased gastrointestinal bleeding; however, this finding was not confirmed by subsequent studies . Nonselective β-blockers are associated with reduced bleeding from gastroesophageal varices in patients with cirrhosis, but in more general populations, β-blockers are not associated with upper gastrointestinal bleeding …”
Section: Discussionmentioning
confidence: 99%
“…GIB can affect the prognosis of AMI patients and increase the risk of major adverse cardiac events (MACEs) in the early stage (during hospitalization and within 30 days after discharge) and late stage (10)(11)(12). GIB is associated with markedly increased mortality and morbidity and can be life-threatening in patients with acute coronary syndromes (ACSs) (13). However, there is no systematic report on the risk factors and prognosis of GIB in AMI patients in China.…”
Section: Introductionmentioning
confidence: 99%